EVALUASI IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA LAPORAN KEUANGAN UMKM DI UNTAG - Sudarynianto Nurathaya Sutarto; Hwihanus, Hwihanus (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze the understanding of Micro, Small, and Medium Enterprises (MSMEs) actors on the implementation of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) and its impact on the quality of the financial reports prepared. Using a descriptive qualitative approach with a case study method, this research was conducted in MSMEs located at the University of August 17 Surabaya. Data was collected through in-depth interviews, observations, and documentation. The results of the study show that the understanding of MSME actors towards SAK ETAP is still limited, with many facing obstacles in its implementation. Factors such as low accounting literacy, limited training, and lack of technical support are the main obstacles. This study recommends the need for more intensive accounting training and support from related parties to improve the quality of MSME financial reports.